It is not just your opinion. Gender equity endorsement of Latin American students and their peers at school - Natalia López-Hornickel; Diego Carrasco; Siugmin Lay; Ernesto Treviño (Large-scale Assessments in Education)
Abstract Promoting adhesion to attitudes toward gender equity is critical to achieving more equal societies, yet endorsement of gender equality among Latin American adolescents remains lower than global averages. This study investigates the role of school environments, civic knowledge, and authoritarianism in shaping gender equity attitudes among 8th-grade students in Chile, Colombia, the Dominican Republic, Mexico and Peru, using data from the International Civic and Citizenship Education Study (ICCS) 2016. Fitting different regression models, we explore the relationships between individual socioeconomic status, classroom practices, and school-wide ideological climates on gender equity endorsement. Findings highlight the pivotal influence of civic knowledge and open classroom discussions as protective factors against authoritarian beliefs, which are negatively associated with gender equity support at both individual and contextual levels. Moreover, peer-group ideological climates significantly shape student attitudes, demonstrating the importance of school environments in fostering or hindering egalitarian beliefs. We discussed the role of school practices in the promotion of gender equity. These findings contribute to the global goal of citizenship education and the Sustainable Development Goals (SDG), particularly Goal 5, emphasising the role of schools in promoting democratic and gender-equitable values.